Efektifitas Peran Otoritas Jasa Keuangan (OJK) terhadap Pengawasan Pendaftaran Jaminan Fidusia di Kota Kendari - Andi Novita Mudriani Djaoe (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
As the times are more advanced, human needs for food and clothing also increased. Even the fulfillment of equipment to support business activities becomes a basic necessity today. One way to satisfy these requirements is to conduct a transaction with a loan secured by the fiduciary models. This study aims to analyze the role of the Financial Services Authority in accordance with the Southeast Sulawesi UU.No.21 Year 2011 on the Financial Services Authority the registration of fiduciary oversight and knowing perfentif efforts undertaken by the Financial Services Authority against registration of fiduciary. This research was conducted in the Office of Financial Services Authority and Southeast Sulawesi Regional Office of the Ministry of Law and Human Rights in Kendari in Southeast Sulawesi. This study uses empirical study of normative law. The method used is the approach of legislation and conceptual approaches. Data obtained in the form of primary data and secondary data was analyzed qualitatively and quantitatively. The results showed that the Financial Services Authority have an important role in the financial sector, but from the point of civil Financial Services Authority can only oversee the fiduciary transactions in which one side is the financing institution. Efforts perfentif to the Financial Services Authority to do in terms of registration of fiduciary guarantee is subject to the regulatory process in a way able to request information or documents contained in the Ministry of Justice and Human Rights on the other hand can terminate the process of filing an application for registration of fiduciary guarantee and sanctions as a last resort.